Remaining Futureproof: Lasting Librarian Roles in Managing Digital Collections. Issue 3 (2nd October 2021) - Kiszl, Péter; Fodor, János
ABSTRACT: From the students' reactions, trainers recognize the changing technological, social, and economic context of library and information science (LIS) and the students' competence expectations. They incorporate these experiences when updating the training program, and draw important conclusions therefrom regarding the future of libraries and LIS. This is crucial to providing students with a credible vision: where is LIS headed; what is the future library like; what roles will libraries have in the era of artificial intelligence, virtual reality, and data science? It is not enough to deny stereotyped predictions, for example, that robotics may take their jobs. In our study we rely on our experiences from courses on digital collections to refute incorrect assumptions and to introduce the four futureproof attributes of LIS: (1) human creativity remains essential; (2) the professional use of social media is crucial in accessing community knowledge; (3) collaboration competences have lasting value; (4) research-oriented attitude is increasingly important in the librarian profession.